Political economy of institutions, democracy and voting - Schofield, Norman 1944-; Caballero, Gonzalo; SpringerLink (Online Service). (Berlin Heidelberg New York Springer, 2011)
This book presents the latest research  in the field of Political Economy, dealing with the integration of economics and politics and the way institutions affect social decisions. The authors are eminent scholars from the U.S., Canada, Britain, Spain, Italy, Mexico and the Philippines. Many of them have been influenced by Nobel laureate Douglass North, who pioneered the new institutional social sciences, or by William H. Riker who contributed to the field of positive political theory. The book focuses on topics such as: case studies in institutional analysis; research on war and the formation of states; the analysis of corruption; new techniques for analyzing elections, involving game theory and empirical methods; comparing elections under plurality and proportional rule, and in developed and new democracies.
PART II: Democracy and voting Empirical and formal models of the United States presidential elections in 2000 and 2004 Normal Schofield, Christopher Claassen, Maria Gallego, and Ugur Ozdemir Modelling elections in post-communist regimes: voter perceptions, political leaders and activists Norman Schofield, JeeSeon Jeon, Marina Muskhelishvili, Ugur Ozdemir, and Margit Tavits Electoral institutions and political corruption: ballot structure, electoral formula, and graft Daniel Max Kselman A model of party entry in parliamentary systems with proportional representation Daniel M. Kselman and Joshua A. Tucker Moving in time: legislative party switching as time-contingent choice Carol Mershon and Olga Shvetsova On the distribution of particularistic goods Jon X. Eguia and Antonio Nicolo Vote revelation: empirical content of scoring rules Andrei Gomberg
Includes bibliographical references
Electronic reproduction
Keywords: Political science; Economics